Sesamin Stimulates Osteoblast Differentiation Through p38 and ERK1/2 MAPK Signaling Pathways - Wanachewin O. (2014)
Background: Osteoporosis is a worldwide health problem predominantly affecting post-menopausal women. Therapies aimed at increasing bone mass in osteoporetic patients lag behind comparable investigation of therapeutic strategies focusing on the bone resorption process. Sesamin, a major lignan compound found in Sesamun indicum Linn., has a variety of pharmacological effects, though its activity on bone cell function is unclear. Herein we examine the effect of this lignan on osteoblast differentiation and function.Method: Cell cytotoxicity and proliferative in hFOB1.19 were examined by MTT and alamar blue assay up to 96 h of treatment. Gene expression of COL1, ALP, BMP-2, Runx2, OC, RANKL and OPG were detected after 24 h of sesamin treatment. ALP activity was measured at day 7, 14 and 21 of cultured. For mineralized assay, ADSCs were cultured in the presence of osteogenic media supplement with or without sesamin for 21 days and then stained with Alizarin Red S. MAPK signaling pathway activation was observed by using western blotting.Results: Sesamin promoted the gene expression of COL1, ALP, OCN, BMP-2 and Runx2 in hFOB1.19. On the other hand, sesamin was able to up-regulate OPG and down-regulate RANKL gene expression. ALP activity also significantly increased after sesamin treatment. Interestingly, sesamin induced formation of mineralized nodules in adipose derived stem cells (ADSCs) as observed by Alizarin Red S staining; this implies that sesamin has anabolic effects both on progenitor and committed cell stages of osteoblasts. Western blotting data showed that sesamin activated phosphorylation of p38 and ERK1/2 in hFOB1.19.Conclusions: The data suggest that sesamin has the ability to trigger osteoblast differentiation by activation of the p38 and ERK MAPK signaling pathway and possibly indirectly regulate osteoclast development via the expression of OPG and RANKL in osteoblasts. Therefore, sesamin may be a promising phytochemical that could be developed for supplementation of osteoporotic therapy. © 2012 Wanachewin et al.; licensee BioMed Central Ltd.